2010
DOI: 10.1590/s0080-62342010000400028
|View full text |Cite
|
Sign up to set email alerts
|

Fadiga entre estudantes de graduação em enfermagem

Abstract: Fatigue among students may harm their learning. This study evaluated the fatigue of nursing undergraduate students and its relations to their graduation year, participation in extracurricular activities, people with whom they lived, depression and their body mass index (BMI)). The study had the participation of 189 (60.2%) students from the EEUSP, from which 96.2% were women with the average age of 21.6 years old, 80.9% lived with their parents, 43.9% performed extracurricular activities, 24.8% had varied BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 11 publications
0
15
0
12
Order By: Relevance
“…In a previous study, the participation of students in extra-curricular activities was considered simply as a contribution to the curriculum or a way to fulfill the complementing hours required by the course, and it was also seen as an obligation. 22 However, the participation in extra-curricular activities during professional training enables students to see and be an integral part of reality, which is full of conflicts and contradictions, and it also encourages them to take part in activities related to their professional choice and to appreciate the importance of their actions. 23 In addition, it was also found that students who intended to withdraw from the course had a lower degree of satisfaction with the program, the institution and the opportunity of development.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the participation of students in extra-curricular activities was considered simply as a contribution to the curriculum or a way to fulfill the complementing hours required by the course, and it was also seen as an obligation. 22 However, the participation in extra-curricular activities during professional training enables students to see and be an integral part of reality, which is full of conflicts and contradictions, and it also encourages them to take part in activities related to their professional choice and to appreciate the importance of their actions. 23 In addition, it was also found that students who intended to withdraw from the course had a lower degree of satisfaction with the program, the institution and the opportunity of development.…”
Section: Discussionmentioning
confidence: 99%
“…Porém, um estudo sobre qualidade de vida relacionada à saúde e sintomas depressivos de estudantes de graduação em enfermagem indicou prejuízo multidimensional na qualidade de vida e observou-se que o impacto negativo na percepção de bem-estar é maior nos estudantes do último ano do curso (23) . Destacam-se como estressores pouca/nenhuma oportunidade para o lazer, agenda lotada, experiência clínica/estágios, currículo da instituição, sobrecarga de atividades, distância diária percorrida entre a residência e a universidade, período integral do curso, falta de tempo para atividades extracurriculares, desorganização das disciplinas, relacionamento conflituoso com os docentes, alto grau de exigência durante o período dos estágios curriculares, curtos prazos para entrega de trabalhos, falta de ética profissional, competitividade entre os alunos, gastos financeiros, atraso no tempo de formação, superlotação das classes e situações que requerem relação interpessoal (13,17,21,22,(24)(25)(26)(28)(29)(30)32,33) . Estes fatores estressores podem ocasionar desordens psicológicas e físicas (fadiga, ansiedade e cansaço), afetando a vida acadêmica e em consequência o futuro profissional, pois há comprometimento do cotidiano do aluno.…”
Section: Resultsunclassified
“…These results are reported by another study that shows professional qualification can trigger insecurity among senior students, once they assume their roles as nurses and experience the challenges and responsibilities of professional life. 27 The feelings of insecurity senior students experience emerge from their perceptions of a lack of ability to meet the demands of professors in regard to practical activities. 20 Professors' demands concerning level of knowledge lead students to perceive their practice as insufficient, leading them to consider dropping out of the program, as they believe they will not be able to meet their professors' expectations.…”
mentioning
confidence: 99%
“…[18][19] The complex assessment systems and level of difficulty demanded in both tests and tasks, as well as theoretical and practical characteristics, are considered sources of stress in the academic environment. 22 Additionally, the relationship between teaching methods and the theoretical content of classes, [27][28] together with a daily overload of tasks and a lack of time to perform all the activities required, are important sources of academic stress. 29 Environmental and professional relationships were also perceived by this study's participants as stress triggers due to the characteristics of the clinical environment, as well as communication and interaction difficulties experienced with professionals during supervised training and practical activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation